Family relational dynamics and young adult outcomes: the mediating role of adolescent emotion regulation - DeWee, Hazel Lee-Ann (My University, 2026)
Family relational dynamics play a crucial role in adolescents’ emotional functioning and later adjustment; however, it remains unclear how adolescents’ emotion regulation shapes the association between family dynamics and young adult well-being. This study examined whether adolescents’ emotion regulation mediates the longitudinal association between parent-adolescent connectedness (Parent 1 = primary caregiver, Parent 2 = other caregiver), parental conflict and triangulation, and young adult life satisfaction and depression, controlling for adolescent biological sex. Utilizing data from the Flourishing Families Project (N = 647; 50.9% female; M age = 11.33, SD = 1.02), structural equation modeling revealed a good-fitting model. Parent 1-adolescent connectedness at Wave 1 predicted greater young adult life satisfaction at Wave 10, whereas parental conflict at Wave 1 was indirectly associated with both young adult life satisfaction and depressive symptoms at Wave 10 through adolescent emotion regulation at Wave 3. Females reported lower emotion regulation, higher depressive symptoms, and greater life satisfaction in young adulthood compared to males. Results underscore the importance of parents’ role in adolescents’ emotional development, with a strong parent-adolescent relationship and lower parental conflict supporting emotion regulation and long-term well-being.
Keywords: Adolescent emotion regulation; Family relational dynamics; Parental conflict; Parental triangulation; Parent-adolescent connectedness; Young adult depression; Young adult life satisfaction; Young adult well-being